Prove that (n-1)^2 divides n^k -1

  • Thread starter popitar
  • Start date
In summary, we need to prove that (n-1)^2 divides n^k-1 if and only if (n-1) divides k. This can be done by using the Euler phi function and Lagrange's theorem. By Euler's theorem, we know that n^phi((n-1)^2) is congruent to 1 mod (n-1)^2. Using Lagrange's theorem, we can see that either k = (n-1)phi(n-1) or k = (n-1)phi(n-1)w. Therefore, n^k is congruent to 1 mod (n-1)^2. This implies that (n-1)^2
  • #1
popitar
17
0
Let n>=2 and k>0 be integers. Prove that (n-1)^2 divides n^k -1 if and only if (n-1) divides k.
 
Physics news on Phys.org
  • #2
you may want to check [tex]\varphi{([n-1]^2)}[/tex]
 
  • #3
I know that (n-1)^2 | (n^k-1) means that (n-1)^2 *m= (n-1)(n^[k-1]+n^[k-2]+...+n+1). But how do I connect this with (n-1)*a=k? Thanks.
 
  • #4
al-mahed said:
you may want to check [tex]\varphi{([n-1]^2)}[/tex]

How do I check it?
 
  • #5
popitar said:
How do I check it?

this is an implication "if and only if", <==>

I'll do the part <==, then you try to do the part ==>

prove that if n-1|k, then [tex](n-1)^2|n^k-1[/tex]:

proof:

first what is [tex]\varphi{([n-1]^2)}[/tex] ??

it is [tex](n-1)^{2-1}\cdot \varphi{(n-1)}=(n-1)\cdot \varphi{(n-1)}[/tex]

now, by euler, as [tex]gcd(n-1,\ n)=1[/tex] then

[tex]n^{\varphi{([n-1]^2)}}=n^{(n-1)\cdot \varphi{(n-1)}}\equiv\ 1\ mod\ (n-1)^2[/tex]

and by Lagrange we know that either [tex]k=(n-1)\cdot \varphi{(n-1)}[/tex] or [tex]wk=(n-1)\cdot \varphi{(n-1)}[/tex]

notice that [tex]\varphi{(n-1)}<n-1<k[/tex], and by hipothesis n-1|k

EDIT: conclusion is: therefore [tex]n^k\equiv\ 1\ mod\ (n-1)^2[/tex]
 
  • #6
Thank you! But at this moment we didnt study anything about Phi function. Do you know any other method?
 
  • #7
al-mahed said:
(...)and by Lagrange we know that either [tex]k=(n-1)\cdot \varphi{(n-1)}[/tex] or [tex]wk=(n-1)\cdot \varphi{(n-1)}[/tex]

oops, in fact it is

(...)and by Lagrange we know that either [tex]k=(n-1)\cdot \varphi{(n-1)}[/tex] or [tex]k=(n-1)\cdot \varphi{(n-1)}w[/tex]

popitar, try to rewrite and "play" with the equations you know related to it, factoring x^k-1 is a way, did your teacher give any similar problem with solutions?
 
  • #8
Thank you so much, Al-Mahed!
Factoring x^k - 1 is (x-1)(x^[k-1]+x^[k-2]+...+x+1), and I see that (x-1)^2 divides x^k-1means that (x-1) divides (x^[k-1]+x^[k-2]+...+x+1), but I don't see how I connect this with (x-1) divides k..
 
  • #9
popitar said:
Thank you so much, Al-Mahed!
Factoring x^k - 1 is (x-1)(x^[k-1]+x^[k-2]+...+x+1), and I see that (x-1)^2 divides x^k-1means that (x-1) divides (x^[k-1]+x^[k-2]+...+x+1), but I don't see how I connect this with (x-1) divides k..


how many elements you have in x^[k-1]+x^[k-2]+...+x+1 ?
 
  • #10
I believe k elements.
 
  • #11
popitar said:
I believe k elements.


correct, k elements, now you must show some work on it, grab a coffe (if you like) and think about it

hint: what means "x-1 divide k" in terms of euclidian form a=qb+r? how could you WRITE it down as an equation? and how to use it? you already saw by yourself you need to prove that x-1 divide x^[k-1]+x^[k-2]+...+x+1
 
  • #12
(x-1) divides k means (x-1) * p = k for some p positive integer. Then I multiply it by (x-1) I get the following (x-1)^2*p=k*(x-1). Then I can say that x^k-1 = k*(x-1)? But (x-1)*z=x^[k-1]+x^[k-2]+...+x+1.. ahh
 
  • #13
This is all I have
(x-1)^2 | x^k - 1 <=> (x-1)|k
(x-1)^2 * m = x^k -1 <=> (x-1)*z=k
(x-1)^2 *m = (x-1)(x^[k-1]+x^[k-2]+...+x+1) <=> (x-1)*z=k
(x-1)*m = x^[k-1]+x^[k-2]+...+x+1 <=> (x-1)*z=k
 
  • #14
write x-1=a, then k=ma=m(x-1) for some integer m, since x-1| k, it yields x=a+1

x^[k-1]+x^[k-2]+...+x+1 = (a+1)^[k-1]+(a+1)^[k-2]+...+(a+1)+1 = a*S + k=(x-1)S+m(x-1), since you'll have k 1's, and the rest of it multiplied by a
 
  • #15
Can you explain this part :(a+1)^[k-1]+(a+1)^[k-2]+...+(a+1)+1 = a*S + k?
 
  • #16
Ok. So you said I replace (x-1) by a, and x=a+1
(x-1)^2 | x^k - 1 <=> (x-1)|k
(x-1)^2 * m = x^k -1 <=> (x-1)*z=k
(x-1)^2 *m = (x-1)(x^[k-1]+x^[k-2]+...+x+1) <=> (x-1)*z=k
(x-1)*m = x^[k-1]+x^[k-2]+...+x+1 <=> (x-1)*z=k
a*m=(a+1)^[k-1]+(a+1)^[k-2] + ...+ (a+1)+1 <=> a*z=k
And from here what to do? Thanks!
 
  • #17
Prove that a divides bc if and only if a/(gcd(a,b)) divides b.
 
  • #18
We need to proofs:
1). If a|bc then a/d divides b, where d = gcd(a,b).
2). If a/d divides b then a|bc.
 
  • #19
popitar said:
Can you explain this part :(a+1)^[k-1]+(a+1)^[k-2]+...+(a+1)+1 = a*S + k?

Popitar, I'm not a teacher, I don't even have a major in mathematics, I'm just a curious guy, so you have to check all this stuff with your teacher.

Anyway, I think you are having trouble to understand the basic concepts of proof, but don't worry, you'll get it soon enough (it is quite confusing at the beginning).

You have to understand the binomial theorem, its expansion, to see that you'll have all the expression being divisible by a=x-1. So if a valid substitution yields a multiple of x-1 you're done in your demonstration that x-1 divide the expression, as required.

Now I think is a good idea turn out the internet and get pencil and paper... try to figure out some stuff by yourself now! Use a calculator to verify some ideas, you need to study more the basics, the euclidian algorithm is the most important thing right now.

That's the stuff you must study now in order to advance.


take care
 

1. What does (n-1)^2 divides n^k -1 mean?

It means that the expression n^k - 1 is divisible by (n-1)^2 without leaving any remainder.

2. What is the significance of proving that (n-1)^2 divides n^k -1?

This expression is commonly used in number theory and has various applications in cryptography, coding theory, and other mathematical fields.

3. How can I prove that (n-1)^2 divides n^k -1?

There are multiple ways to prove this statement, including using mathematical induction, polynomial division, or the binomial theorem.

4. Is this statement true for all values of n and k?

Yes, this statement holds true for all positive integer values of n and k.

5. Can you provide an example to illustrate this statement?

Sure, for n=3 and k=4, (n-1)^2 = (3-1)^2 = 4, and n^k - 1 = 81-1 = 80. Since 80 is divisible by 4 without any remainder, we can say that (n-1)^2 divides n^k -1 in this case.

Similar threads

  • Linear and Abstract Algebra
Replies
2
Views
964
  • Linear and Abstract Algebra
Replies
1
Views
617
  • Linear and Abstract Algebra
Replies
12
Views
1K
  • Linear and Abstract Algebra
Replies
4
Views
874
  • Linear and Abstract Algebra
Replies
4
Views
1K
  • Linear and Abstract Algebra
Replies
8
Views
747
  • Linear and Abstract Algebra
Replies
25
Views
1K
  • Linear and Abstract Algebra
Replies
3
Views
1K
  • Precalculus Mathematics Homework Help
Replies
6
Views
1K
  • Linear and Abstract Algebra
Replies
11
Views
1K
Back
Top